2015
DOI: 10.1186/s12883-015-0434-x
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of neural tracts in a patient with CADASIL: a diffusion tensor imaging study

Abstract: BackgroundWe report a patient with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), who showed injuries of the neural tracts, which was demonstrated by diffusion tensor tractography (DTT).Case presentationA 64-year-old male patient and seven age-matched control volunteers were recruited. Since approximately 1.5 years ago, he had felt mild weakness of the right arm and was diagnosed as CADASIL by the finding of the exon 11 mutation of the NOTCH3 gene approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Accordingly, the present study reveals that as compared to a group of healthy controls, patients with CADASIL show widespread significant changes of the DTI‐derived indices in WM tracts. This in line with the observation in a single case of CADASIL examined with tractography . The results of this between group analysis in consideration of the above neuropathological descriptions justifies the assumption that the DTI changes we observed correspond to the microstructural damage in CADASIL …”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, the present study reveals that as compared to a group of healthy controls, patients with CADASIL show widespread significant changes of the DTI‐derived indices in WM tracts. This in line with the observation in a single case of CADASIL examined with tractography . The results of this between group analysis in consideration of the above neuropathological descriptions justifies the assumption that the DTI changes we observed correspond to the microstructural damage in CADASIL …”
Section: Discussionsupporting
confidence: 90%
“…In Tract 2, the left CST showed a discontinuation to the cerebral cortex and a disconnection below the lower pons compared to Tract 1 (Figure 2B,Ca). As in previous studies, DTT parameter values (FA, MD, and TV) indicating a deviation of more or less than two standard deviations(SDs) compared with control subjects were defined as abnormal [9,10]. The majority of the left CST exhibited lower FA and TV values than SDs and higher MD values than two SDs.…”
Section: Diffusion Tensor Tractographymentioning
confidence: 90%
“…Diffusion tensor imaging (DTI) studies have demonstrated widespread white matter lesions associated with cognitive deficits in CADASIL ( 13 15 ). Moreover, a case study using diffusion tensor tractography indicated that neural tract injuries were mainly located in the frontal lobe in a patient with CADASIL ( 16 ). Furthermore, a recent 18 F-2-fluoro-2-deoxy- d -glucose PET ( 18 F-FDG PET) study showed that decreased metabolism in the limbic lobe, including the hippocampus and PHC, was positively associated with a cognitive score in patients with CADASIL ( 17 ).…”
Section: Introductionmentioning
confidence: 99%